2015
DOI: 10.4088/jcp.14l09462
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Management of Treatment-Resistant Depression

Abstract: To the Editor: Approximately one-third of patients with major depressive disorder (MDD) are treatment resistant. 1,2 Despite high prevalence, the clinical characteristics and management of treatment-resistant depression (TRD) are not well described. We present a comprehensive clinical description of a case series of 79 well-characterized patients with TRD referred to a university-based TRD specialty clinic.Method. Of 104 patients referred to our TRD clinic from 2009 to 2014, 79 met clinic inclusion criteria: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Results of this study manifested that the total course of disease of the TRD patients was longer than that of the non-TRD patients, and the onset age was lower than that of the non-TRD patients before treatment. Conway et al (5) found that the course of disease of TRD patients is longer, suggesting that the disease of such patients is more likely to be chronic. According to the study of Juruena et al (6), it was also confirmed that the longer the single course of TRD in patients is, the worse the recovery of social function will be.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study manifested that the total course of disease of the TRD patients was longer than that of the non-TRD patients, and the onset age was lower than that of the non-TRD patients before treatment. Conway et al (5) found that the course of disease of TRD patients is longer, suggesting that the disease of such patients is more likely to be chronic. According to the study of Juruena et al (6), it was also confirmed that the longer the single course of TRD in patients is, the worse the recovery of social function will be.…”
Section: Discussionmentioning
confidence: 99%
“…Observations on the first 79 patients evaluated in the TRMD Clinic have been reported elsewhere ( 25 ) but are instructive and relevant to the pilot clinical study of nitrous oxide described below. Patients seen in the TRMD Clinic range in age from 19 to 85 years and have an early onset of MDD, averaging 24.3 years of age at onset.…”
Section: Treatment-resistant Major Depressionmentioning
confidence: 97%
“…In an effort to deal with the common problem of TRMD and its complexity, Conway and colleagues ( 25 ) established the Washington University TRMD Clinic. The goal of this clinic is to provide a systematic and comprehensive evaluation and consultation program for persons with well defined TRMD, focusing primarily on patients with pure unipolar MDD.…”
Section: Treatment-resistant Major Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of monoamine oxidase inhibitors (MAOIs) as an effective treatment for depression dates back to the 1950s. [1][2][3][4] The subsequent decades marked the discovery of more potent inhibitors that provided enhanced selectivity between isozymes MAO-A and MAO-B and had reversible binding with MAO. 5 However, safety concerns have markedly decreased their use in recent years, necessitating the search for alternative MAOIs.…”
Section: Introductionmentioning
confidence: 99%